2006
DOI: 10.1521/aeap.2006.18.supp.96
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Effective HIV Prevention Interventions–Lessons from Maryland and Massachusetts

Abstract: This article describes, compares, and contrasts the contexts, processes, and results of the experiences of Maryland and Massachusetts in diffusing evidence-based interventions. The evolution of first Maryland's, then Massachusetts's, diffusion of effective interventions is described. Both states have extensive experience planning, developing and evaluating individual-, group-, and community-level interventions promoted in the Centers for Disease Control and Prevention's Diffusion of Effective Behavioral Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Thousands of community-based organizational personnel have been trained in the use of one or more of the compendium's programs (Collins 2009;Collins et al 2006). State, territorial, and local health departments increasingly encourage applicant organizations to select among these programs as the basis for continued prevention funding (see, for example, Peterson and Randall 2006;Shea et al 2006), whether or not specific evidencebased programs for organizations' target populations are available.…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of community-based organizational personnel have been trained in the use of one or more of the compendium's programs (Collins 2009;Collins et al 2006). State, territorial, and local health departments increasingly encourage applicant organizations to select among these programs as the basis for continued prevention funding (see, for example, Peterson and Randall 2006;Shea et al 2006), whether or not specific evidencebased programs for organizations' target populations are available.…”
Section: Introductionmentioning
confidence: 99%
“…Agencies are encouraged to develop an intervention implementation plan, provide ongoing leadership to the intervention from within the agency, solicit staff feedback and suggestions for addressing delivery problems encountered, provide additional training to staff to be able to deliver the intervention, ensure fidelity to core elements, and monitor client responsiveness to the interventions as part of quality assurance. In practice, agencies that are using CDC-recommended interventions vary in the extent to which they conduct these pre-implementation and implementation steps [14,15]. Compiling a clear picture of changes made during intervention pre-implementation through maintenance phases can inform the development of future guidance for agencies and can illuminate reasons for increased or decreased intervention effectiveness in preventing HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have observed that characteristics of the intervention may serve as barriers: for example, lack of teaching materials and materials that are easy to use, limited access to training, and restrictions on modifying the intervention 9,10. Barriers reported by public health departments include the limited availability of EBIs and cost-effective technical assistance and failure to cross-train CBO staff 11,12. Scant research has been conducted on how common these challenges are across CBOs or how they are resolved as EBIs are scaled for implementation 13,14.…”
mentioning
confidence: 99%